PERANCANGAN MOBILE GAME BERDASARKAN PERMAINAN RAKYAT â€œDODOMBAANâ€ UNTUK MEMBANGUN INTERAKSI SOSIAL ANTAR PEMAIN - RAYMOND RALIBI; ACHMAD SYARIEF; IRFANSYAH IRFANSYAH (Serat Rupa: Journal of Design, 2016)
ABSTRACTâ€œDodombaanâ€ is an old and popular folk-game amongst children in West Java, although nowadays it becomes rarely played as many children are in favor of playing digital games. Scholars believe that this folk-game actually provides an opportunity for children to develop a sense of social-sensitiveness, as children interactively play with each other. Having exposed to children interests on digital games and the social benefit of Sundanese folk-game, the study sets to design and develop a digital-game based on Sundanese folk-game of dodombaan. This design-study started by collecting and analyzing data of users and plays of dodombaan, which iteratively done in support of the process of designing a digital game. The formal elements of game are composed according to the original game-play of dodombaan. This is to assure that users will have similar game-experiences and social-benefit of the play. The digital game of dodombaan is developed as a mobile multi-player game on android platform and visualized according to the traditional art of sheepâ€™s battle (seni ketangkasan domba) of Garut West Java. It is expected that the developed game of dodombaan can serve as an alternative product of digital game with cultural contents.Â Keywords: cultural content game; multiplayer mobile games; Sundanese folk-gameÂ